Unexpected diversity of Lacon Laporte, 1838 (Coleoptera: Elateridae: Agrypninae) in the Levant: revised species concepts, new species, and an identification key - Kundrata, Robin; Mertlik, Josef; Németh, Tamás (Zootaxa, 2019)
The species of genus Lacon Laporte, 1838 from the Levant are taxonomically revised. Currently, 18 species are known from the area covering the island of Cyprus and mainland from Hatay province of Turkey to Israel. Six species are described as new for science: Lacon mucheibensis sp. nov. (Israel), L. qatanensis sp. nov. (Syria), L. platiai sp. nov. (Jordan), L. safitensis sp. nov. (Syria), L. tafilensis sp. nov. (Jordan), and L. zenobiae sp. nov. (Lebanon, Syria). Lacon freidbergi Platia, 2010 is synonymized with L. lithophilus (Candèze, 1857), and L. kapleri Platia & Schimmel, 1994 with L. graecus (Candèze, 1857). Lacon drusus (Marseul, 1870) is recorded for the first time from Israel. Lacon lithophilus is recorded for the first time from Israel and Jordan. Lacon graecus is removed from the fauna of Levant, because all earlier reports of this species from Lebanon and Syria were based on misidentifications. Figures of habitus and main diagnostic features are provided for all species and an identification key to the Lacon species of the Levant is given.